2023
DOI: 10.1097/mol.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Circulating protein and lipid markers of early sepsis diagnosis and prognosis: a scoping review

Abstract: Purpose of reviewSepsis is the extreme response to infection associated with high mortality, yet reliable biomarkers for its identification and stratification are lacking.Recent findingsOur scoping review of studies published from January 2017 to September 2022 that investigated circulating protein and lipid markers to inform non-COVID-19 sepsis diagnosis and prognosis identified interleukin (IL)-6, IL-8, heparin-binding protein (HBP), and angiopoietin-2 as having the most evidence. Biomarkers can be grouped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“… 36 Barber et al also found that low HDL is associated with poor outcome in sepsis. 37 We recommend the utility of plasma TG as a prognostic marker. Lipid mediators play an important role in the proinflammatory and counter-regulatory anti-inflammatory changes in the microvasculature in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Barber et al also found that low HDL is associated with poor outcome in sepsis. 37 We recommend the utility of plasma TG as a prognostic marker. Lipid mediators play an important role in the proinflammatory and counter-regulatory anti-inflammatory changes in the microvasculature in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid progression and high mortality of sepsis implies the necessity of identifying prognostic indicators associated with its outcome. It is recommended that scholars further explore serum markers and prognostic correlates to help clinicians intervene early [16,17] . Calcium is an essential trace element in the human body that is responsible for physiological functions including cell signaling, neurotransmission, and muscle contraction [6,18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it enhances endothelial cell permeability in many parts of the body, thereby assisting inflammatory cell migration to and aggregation at the infection source. 11 However, excessive HBP leads to vascular leakage, edema, and immune disorder in severe infections. 12,13 Increased levels of HBP in peripheral blood have been reported as a common feature of patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%